A community‐specific framework of risk factors for youth violence: A qualitative comparison of community stakeholder perspectives in a low‐income, urban community. Issue 5 (3rd January 2021) - Ross, Katherine M.; Sullivan, Terri; O'Connor, Kelly; Hitti, Stephanie; Leiva, Manuel N.
Abstract: This study offers a qualitative comparison of risk factors for youth violence from the perspectives of community stakeholders in a low‐income, urban community experiencing elevated rates of violence. One‐on‐one interviews were conducted with 36 community stakeholders across three key categories: 10 community residents who cared for youth living in the community, 15 program or service providers, and 11 leaders in community agencies and organizations. A grounded theory approach was used for data collection and analysis to extract themes that emerged from the question, " What are the things in the community that lead to youth violence? " While there was significant overlap in stakeholders' beliefs about precursors to youth violence, important differences also emerged. In order for youth violence prevention strategies to be successful, they must consider and address risk factors identified by community stakeholders involved in the implementation and sustainability.